2018
DOI: 10.1093/icb/icy022
|View full text |Cite
|
Sign up to set email alerts
|

Do Seasonal Glucocorticoid Changes Depend on Reproductive Investment? A Comparative Approach in Birds

Abstract: Animals go through different life history stages such as reproduction, moult, or migration, of which some are more energy-demanding than others. Baseline concentrations of glucocorticoid hormones increase during moderate, predictable challenges and thus are expected to be higher when seasonal energy demands increase, such as during reproduction. By contrast, stress-induced glucocorticoids prioritize a survival mode that includes reproductive inhibition. Thus, many species down-regulate stress-induced glucocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 62 publications
3
19
0
Order By: Relevance
“…Be-cause elevated GCs can be particularly costly to reproduction, this pattern could reflect a protective role of GC evolution reducing stress-induced levels more in the sex that tends to invest more in each reproductive attempt. Most previous phylogenetically informed analyses of steroid hormones have either included males only or averaged data from both sexes, but two analyses in birds support this hypothesis (Bókony et al 2009;Casagrande et al 2018). Our finding that sex does not predict baseline GCs across tetrapods is consistent with patterns observed in mammals (Haase et al 2016) but not in birds (Casagrande et al 2018).…”
Section: Comparing Specific Hypotheses Of Gc Variationsupporting
confidence: 83%
See 1 more Smart Citation
“…Be-cause elevated GCs can be particularly costly to reproduction, this pattern could reflect a protective role of GC evolution reducing stress-induced levels more in the sex that tends to invest more in each reproductive attempt. Most previous phylogenetically informed analyses of steroid hormones have either included males only or averaged data from both sexes, but two analyses in birds support this hypothesis (Bókony et al 2009;Casagrande et al 2018). Our finding that sex does not predict baseline GCs across tetrapods is consistent with patterns observed in mammals (Haase et al 2016) but not in birds (Casagrande et al 2018).…”
Section: Comparing Specific Hypotheses Of Gc Variationsupporting
confidence: 83%
“…These patterns are broadly consistent with the findings of a previous analysis of birds actively engaged in parental care (Bókony et al 2009), which used a metric of brood value that incorporated both longevity and clutch size. A recent analysis, also in birds, which incorporated data from the breeding and nonbreeding seasons, found that clutch size positively predicted baseline but not stress-induced GC levels (Casagrande et al 2018). The presence of this pattern at larger taxonomic scales, and in a data set that includes many measures from species and sexes that do not engage in parental care, suggests that general reproductive investment may be a particularly important driver of variation in GCs across populations and species.…”
Section: Comparing Specific Hypotheses Of Gc Variationmentioning
confidence: 99%
“…R. Soc. B 285: 20182141 challenges, and therefore analysing individual changes (or reaction norms) are perhaps as important as absolute values, or even more important [23,31,[87][88][89][90][91]. The field is now ripe for the development of quantitative predictions for the links between changes in physiology and life-history decisions of individuals.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether GCs play a role in mediating such trade-offs at low baseline concentrations is less clear, although their involvement has been hypothesized [22]. Baseline GCs are elevated when individuals experience increased energetic demands [11,12,17,18,[22][23][24][25], for example, in the reproductive season when parents provision their offspring [18,[26][27][28][29][30][31]. These findings prompted the hypothesis that baseline GCs may mediate trade-offs, but in an opposite way to stress-induced concentrations: baseline GCs would support investment in current reproduction at the expense of survival [22,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…More surprising was the finding of a consistently negative relationship between baseline GC levels and reproductive success. Although elevated baseline GCs are often seen in individuals facing stressors, baseline GCs are also frequently upregulated in advance of energetically demanding life history stages, and are believed to help organisms mobilize energy to meet these demands (Romero, Reed, & Wingfield, 2000; Bonier et al ., 2009a; Casagrande et al ., 2018; Vitousek et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%